CONTENT PROCEDURAL COMPONENTS OF PEDAGOGICAL PERSONNEL TRAINING TO WORK WITH THE FOSTER FAMILY - L. Saenko; G. Solomatina (Вестник Северо-Кавказского федерального университета, 2022)
The article presents ways to increase the effectiveness of raising an orphaned child in the conditions of a substitute family, which should ensure that he is introduced to the basic human values, moral and cultural norms ofsocially approved behavior. One aspect of this problem is training for work with substitute families. The article proposed the directions and content of the program to improve the competence of specialists in different areas of training and qualifications (specialists in the education system, health care and social protection).